"I am African American": Racial-ethnic self-designation, self-concept, and major depression among African Americans. (May 2023) - Nicholson, Harvey L.
Background: Research remains mixed on whether racial-ethnic self-designation impacts psychological health and well-being among Americans of African descent. Existing studies mainly use non-representative samples to address this question. Some scholars argue that Black people who express an African-centered identity should experience improved mental health because it enhances one's sense of self. However, what role self-designation may have on depression, one of the most common forms of disability, is largely unknown among African Americans. There is also limited evidence on whether one's self-concept can help us understand the relationship between self-designation and mental health among African Americans. Methods: Using data from a national probability sample of African American adults ( n  = 3, 329), I examined whether self-designation as African American, Afro-American, Negro, Black American, or some other label versus Black was associated with self-esteem, mastery, and major depressive episodes. Results: Using OLS models, I found that respondents who preferred the terms African American or Afro-American exhibited higher mastery levels compared to individuals who preferred the label Black, the most common term used among respondents. African American identifying respondents also exhibited significantly higher levels of self-esteem compared to Black identifying individuals. Using logistic regression models, I found that only African American identifying respondents were significantly less likely than Black identifying respondents to meet the criteria for major depressive episodes in the past-year. Higher levels of mastery and self-esteem helped to explain such differences. Conclusion: In sum, among Americans of African descent, identification as African American rather than Black may help fight depressive episodes because such self-designation may enhance one's self-concept. Further research is necessary to explore other possible psychological implications of self-designation among the African American/Black population.